OCCURRENCE RATE OF HIGH RISK HISTOLOGICAL FEATURES IN PRIMARY ENUCLEATION SPECIMENS OF PEDIATRIC RETINOBLASTOMA PATIENTS: A LOCAL EXPERIENCE - Sherazi, Natasha; Khurshid, Iram Kehkashan; Niaz, Mahwish; Arif, Hira; Qayyum, Zunaira; Waqar, Maryam (Journal of Ayub Medical College Abbottabad, 2024)
Background: Retinoblastoma, the most common primary intraocular malignancy in childhood, predominantly affects children under the age of five. With an incidence of approximately 1 in 15,000 to 20,000 live births globally, the condition sadly leads to over 3000 childhood deaths annually, with significantly higher mortality rates in Asia and Africa. This study, conducted in the Histopathology Department of Foundation University Medical College, Rawalpindi, over a one-year period (from 25th September 2019 to 24th September 2020), aimed to determine the frequency of high-risk histological features in primary enucleated eye specimens with retinoblastoma to guide therapeutic strategies. A cross-sectional study design was employed, utilizing non-probability consecutive sampling. Methods: After approval from ethical review board, all patients fulfilling the inclusion criteria were enrolled in the study. All the demographic details of the patients including age, gender, duration since the diagnosis and family history of retinoblastoma were obtained. The specimens of retinoblastoma received form eye department were marked. Freshly cut 3-5 microns thick sections stained with Haematoxylin and Eosin (H & E) were examined microscopically by a team of two histopathologists. The presence or absence of high-risk histological features was reported /recorded in the designed proforma. Results: A total of 150 patients were included in the study. The mean age of the patients was found to be 2.51±1.30 years. The gender distribution showed that most of the patients were males. The mean duration since diagnosis was 4.70±2.81 months. Positive choroid invasion was found in 25 patients (16.7%) and optic nerve invasion was found in 77 patients (51.3%). Conclusion: The study showed that optic nerve invasion was found in significant number of patients and was more prevalent than choroid invasion in patients with retinoblastoma. This will help our clinicians to better guide our patients regarding the prognosis of the disease and deciding the treatment options for the patients.